The Consequences of Real Life Practice of Early Abdominal Aortic Aneurysm Repair: A Cost-Benefit Analysis. (July 2017) - Tomee, S.M.; Bastiaannet, E.; Schermerhorn, M.L.; Golledge, J.; Hamming, J.F.; Lindeman, J.H.
Abstract : Background: The reported 54 mm median intervention diameter for endovascular aneurysm repair (EVAR) in the Vascular Quality Initiative and European data from the Pharmaceutical Aneurysm Stabilisation Trial (PHAST) implies that in real life the majority of abdominal aortic aneurysm (AAA) repairs occur at diameters smaller than the consensus intervention threshold of 55 mm. This study explores the potential consequences of this practice. Methods: The differences between real life AAA repair and consensus based intervention threshold were explored in reported data from vascular quality initiatives and PHAST. The subsequent consequences of advancement of endovascular aneurysm repair (EVAR) were estimated using a multistate model based on life tables for the EVAR Medicare population. Results: There appears an approximate 5 mm difference in AAA diameter between real life practice and consensus intervention threshold. Assuming a 2.5 mm annual growth rate, this results in an approximately 2 year advancement of AAA repair. According to the model used, early repair reduces overall small aneurysm patient mortality by 2.3%, it results in 21.9% more EVAR procedures, more EVAR related deaths, and 42.3% and 36.8% more open and endovascular re-interventions, respectively. Cost–benefit estimates imply 482 fewer AAA related deaths, but 140 extra EVAR related deaths for a population of more than 30, 000 AAA patients, and a 300 million USD increase in health costs for the 8 year observation period in the Medicare population. Conclusions: In the real life situation a large proportion of EVAR procedures appear to occur before reaching the consensus threshold. Although this reduces mortality, it comes at a cost of approximately 1 million USD per prevented rupture related death.